Metabolismo nutricional em Atta sexdens rubropilosa Forel, 1908: voo nupcial, fundação e desenvolvimento da colônia - Silva, Edypo Jacob da [UNESP] (2015)
The leaf-cutting ants are important agricultural pests; held annually the foundation of new colonies. The nuptial flight and the nest digging are high intensity activity which consume body reserves. The study goals to: (1) verify the digging effort by measuring the carbohydrate content and total lipids in males and females before and after nuptial flight, and the queen's digging effort during the foundation; (2) study the nests in the claustral phase or the development and the production of CO2 during the foundation and establishment of the nest; (3) determine the crude protein content of the queens of Atta sexdens before the nuptial flight at the claustral phase in laboratory and field colonies. The digging effort was quantified by experimentally stimulating the queens to dig a nest one, two or three consecutive times compared to the queens that did not dig. The colorimetric method was used to determine the soluble carbohydrates and extraction method of immersion was used to determine the total lipids. The study of the nests claustral phase and the CO2 production was done by analyzing the development of the initial 50 colonies of Atta sexdens rubropilosa, and production of expelled carbon dioxide under laboratory conditions. Crude protein was determined by digestion of the organic material with sulfuric acid at high temperatures. Based on our results we conclude that the carbohydrate content is the main energetic resource used for the nuptial flight and nest digging, for gynes of leaf-cutting ants. The concentration of CO2 had a large increase in week six and seven weeks, and then returning to lower values. Protein is used for survival of the queen and for early colony growth, as demonstrated by the reduction in crude protein content as a function of duration of the claustral phase.